PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA KELAS V TEMA LINGKUNGAN SAHABAT KITA SD N 3 DORANG TAHUN PELAJARAN 2020/2021 - Indah Puji Astutik; Joko Susanto; Choirul Huda (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract : Application of the Discovery Learning Learning Model to Improve Learning Outcomes in Class V The Environmental Theme of Our Friends at SD N 3 Dorang for the 2020/2021 Academic Year. PTK. Primary School Teacher Education Department. Teacher Professional Education. Supervisor: Drs. Choirul Huda, M.Pd. The background of the research is the low student learning outcomes in learning. This is because the teacher does not create learning that stimulates student activity. Students just sit, take notes, and listen to what the teacher says while teaching. With such a learning atmosphere, students become bored so that it affects student learning outcomes. This is supported by data on the achievement of learning outcomes for fifth grade students at SD Negeri 3 Dorang that grade V students learning outcomes in the second semester of the Daily Test who achieve the Minimum Completeness Criteria (KKM) are only 5 out of 14 students or 35%. Learning outcomes data are shown with the lowest score of 40 and the highest score of 80, with a class average of 65.8. The formulation of the problem is how to apply the discovery learning model to improve learning outcomes in class V with the theme of the environment of our friends at SD N 3 Dorang for the academic year 2020/2021 For problem solving, the researcher chose the Discovery Learning learning model which can increase student activity so that it also affects the learning outcomes of fifth grade students at SD N 3 Dorang with steps a) Phase 1 Stimulation b) Phase 2 Problem statement c) Phase 3 Data collection d) Phase 4 Data processing e) Phase 5 Verification f) Phase 6 Generalization. The purpose of this study is to improve and improve learning outcomes on the theme of Our Friendly Environment in thematic learning for fifth grade students at SDN 3 Dorang. The benefit is to improve the learning outcomes of fifth grade students of SD N 3 Dorang in thematic learning on the theme of Our Friendship Environment.The results showed an increase in student learning outcomes, namely: The average value in the first cycle of meeting 1 was 64.29 with a percentage of 36%. The average value of the first cycle of meeting 2 is 67.14 with a percentage of 64%. The average value of the second cycle of the first meeting was 69.29 with a percentage of 71%. The average value of the second cycle meeting 2 is 72.14 with a percentage of 79%. The average value of cycle III meeting 1 is 74.29 with a percentage of 86%. The average value of cycle III meeting 2 is 84.29 with a percentage of 100%. The advice given is that the teacher can use the right learning model so that learning can run well and can improve student learning outcomes. Keywords : Learning Outcomes, Model Discovery Learning, Class V The Environmental Theme of Our Friends Abstrak : Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Pada Kelas V Tema Lingkungan Sahabat Kita SD N 3 Dorang Tahun Pelajaran 2020/2021. PTK. Jurusan Pendidikan Guru Sekolah Dasar. Pendidikan Profesi Guru. Dosen Pembimbing: Drs. Choirul Huda, M.Pd. Penelitian dilatarbelakangi karena rendahnya hasil belajar siswa dalam pembelajaran. Hal ini dikarenakan guru tidak menciptakan pembelajaran yang merangsang keaktifan siswa. Siswa hanya duduk, mencatat, dan mendengarkan apa yang disampaikan guru saat mengajar. Dengan suasana pembelajaran yang seperti itu, siswa menjadi bosan sehingga berpengaruh pada hasil belajar peserta didik. Hal itu didukung data data pencapaian hasil belajar peserta didik kelas V di SD Negeri 3 Dorang bahwa peserta didik kelas V hasil belajar pada Ulangan Harian semester II yang mencapai Kriteria Ketuntutasan Minimal (KKM) hanya 5 dari 14 peserta didik atau 35%. Data hasil belajar ditunjukkan dengan nilai terendah 40 dan nilai tertinggi 80, dengan rerata kelas 65,8. Rumusan masalah yaitu Bagaimana Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Pada Kelas V Tema Lingkungan Sahabat Kita SD N 3 Dorang Tahun Pelajaran 2020/2021? Untuk pemecahan masalah, peneliti memilih model pembelajaran Discovery Learning yang dapat meningkatan ke aktifan siswa sehingga berpengaruh juga dengan hasil belajar siswa kelas V SD N 3 Dorang dengan langkah a) Fase 1 Stimulation b) Fase 2 Problem statement c) Fase 3 Data collection d) Fase 4 Data processing e) Fase 5 Verification f) Fase 6 Generalization. Tujuan penelitian ini adalah untuk memperbaiki dan meningkatkan hasil belajar pada tema Lingkungan Sahabat Kita dalam pembelajaran tematik pada Peserta didik kelas V SDN 3 Dorang. Manfaatnya adalah untuk mengingkatkan hasil belajar peserta didik kelas V SD N 3 Dorang pada pembelajaran tematik dalam tema Lingkungan Sahabat Kita.Hasil penelitian menunjukkan adanya peningkatan dalam hasil belajar peserta didik, yaitu : Nilai rata-rata pada siklus I pertemuan 1 sebesar 64,29 dengan prosentase 36%. Nilai rata-rata siklus I pertemuan 2 sebesar 67,14 dengan prosentase 64%. Nilai rata-rata siklus II pertemuan 1 sebesar 69,29 dengan prosentase 71%. Nilai rata-rata siklus II pertemuan 2 sebesar 72,14 dengan prosentase 79%. Nilai rata-rata siklus III pertemuan 1 sebesar 74,29 dengan prosentase 86%. Nilai rata-rata siklus III pertemuan 2 sebesar 84,29 dengan prosentase 100%. Saran yang di berikan yaitu Guru dapat menggunakan model pembelajaran yang tepat agar pembelajaran dapat berjalan dengan baik dan dapat meningkatkan hasil belajar peserta didik. Kata kunci : Hasil Belajar, Model Discovery Learning, Kelas V Tema Lingkungan Sahabat Kita